Utilization and referral pattern at Sidamo Regional Hospital: A one-year prospective registration study in 1985/86 - Lindtjorn, Bernt (My University, 2019)
Hospitals can serve as important complement to Primary Health Care. Periodic reviews of hospital functions are therefore needed. We have reviewed hospital use and referral pattern at a regional hospital in southern Ethiopia. 85 % of admitted patients were from the region, and 2/3 from the local province. The effect of proximity on hospital use is shown but varied for the different patient groups. Patients from the local province were less often referred than patients from the remote provinces. The hospital functions mainly as a local hospital for the Sidamo Province and less as a referral hospital for the other parts of the region. The very large functional catchment area may worsen the local population's access to the hospital.
Keywords: Ethiopia; Hospitals; Referrals